New perspectives and recommendations for anticoagulant therapy post orthopedic surgery - Marcelo Kropf; Cleidson Alves Bergami; Felipe Dias Leal; Claudia Oliveira Dias Passos; Zilda de Santana Gonsalves; Isabela Laudares Marques; Isabela Azevedo Mota; Marcele Lima Monte Gonçalves (Universidade de São Paulo, 2011)
Anticoagulant therapy is essential for the prevention of risks associated with the formation of thrombus in patients after surgery, especially in orthopedics. Recently, new oral anticoagulants were introduced in the therapeutic arsenal. This fact is important, because the current drug of choice in clinical practice is enoxaparin, a low molecular weight heparin. As all injecting drugs, enoxaparin may reduce patients' adherence to treatment by dissatisfaction with and resistance to the administration. This article reviews the available literature on the overall utility of these innovative medicines, approaching the pharmacology, the compared efficacy in relation to current agents, and the potential targets for new agents, as well as points to new trends in research and development. The article also contributes with a practical guide for use and recommendations to health professionals, especially focusing on the reversibility of hemorrhagic events, and discusses the importance of convenience/satisfaction of use, the cost of treatment, and the risk-benefit profile for patients. A terapia anticoagulante é fundamental para a prevenção de riscos associados à formação de trombos em pacientes pós-cirúrgicos, principalmente em ortopedia. Recentemente, novos anticoagulantes orais foram introduzidos no arsenal terapêutico. Tal fato é importantíssimo, visto que o atual medicamento de primeira escolha na prática clínica é a enoxaparina, uma heparina de baixo peso molecular. Por ser de uso injetável, a enoxaparina pode diminuir a adesão do paciente ao tratamento, devido à insatisfação e à resistência quanto à via de administração. Este artigo revisa a literatura disponível sobre a utilidade total desses medicamentos inovadores ao abordar a farmacologia, a eficácia em comparação com os agentes atuais e os alvos potenciais para novos agentes, bem como aponta as novas tendências em pesquisa e desenvolvimento. O artigo também contribui com um guia prático de uso e recomendações aos profissionais de saúde, com um enfoque especial sobre a reversibilidade de eventos hemorrágicos e, finalmente, discute a importância da conveniência/satisfação de uso, o custo de tratamento e o perfil risco-benefício para o paciente.